The Evolution and Impact of Internal Audit Quality: A Systematic Review of Theory, Methodology, and Global Trends - Retna Sari; Syahril Djaddang; Suratno (Agregat: Jurnal Ekonomi dan Bisnis, 2026)
This study aims to explore the evolution of internal audit quality through a systematic literature review (SLR) based on various theories, contexts, and methodologies. In this study, the factors influencing internal audit quality are explored, and current trends in this field are identified. The methodology used was an SLR with a PRISMA approach, which included the identification, screening, and inclusion of articles from the Scopus database. Of the 206 articles found, 21 articles met the inclusion criteria and were further analyzed using thematic analysis. The results of the study show that Agency Theory remains the dominant theory in internal audit quality studies, but there is a significant gap in the application of alternative theories such as Stakeholder Theory. In addition, quantitative methods still dominate, especially in the form of regression and secondary data analysis, although there is a push to integrate qualitative and mixed- methods to understand more complex dynamics. This study also found a concentration of studies in developing countries, particularly in China, indicating a great need to improve internal audit quality in these regions. Overall, this study contributes to expanding the understanding of internal audit quality through a broader synthesis of theory and methodology. The context of developed countries should be considered in future research, and the influence of technology in improving internal audit quality should be further explored. Further research should also integrate other theories to enrich existing perspectives